THE ENGLISH EDUCATION DEPARTMENT STUDENTS PERCEPTIONS OF IDEAL ENGLISH TEACHER IN HIGH SCHOOL LEVEL - Riza Maulana Ardiyanto; Sri Endang Kusmaryati; Farid Noor R. (Jurnal Prakarsa Paedagogia, 2019)
Ideal English teacher is very important in teaching and learning English especially in high schools. According to Indonesia government regulation, an ideal English teacher is an English teacher who has 4 competencies. They are pedagogical, personal, social, and professional competence. This article is a report of the research aims to know the students of English Education Department perception of an ideal English teacher in high school level. It is designed through descriptive qualitative research. To collect the data, the writer use questionnaire. The result of this research shows that according to the students, in pedagogical competence, an ideal English teacher should understand the students’ characteristic. While in personal competence, an ideal English teacher should have high responsibilities. Furthermore, in social competence, the students think that an ideal English teacher should not discriminate the students based on the background of the family. In professional competence, an ideal English teacher should use many sources in delivering the material. Finally, the writer hopes this research can be used by the English teacher as a suggestion to be the truly ideal English teacher.